Personalna przestrzeń wewnętrzna w przywództwie edukacyjnym - Ptak, Małgorzata; Śmiałek, Mirosław (Rocznik Pedagogiczny, 2021)
The space between the subjective and objective fills a person’s identity. It is knowledge about one- self, about the difference between oneself and others / strangers, about one’s own actions, their effects and consequences. It is likewise knowledge of one’s own uniqueness, of the consequences of one’s own actions that define the limits of one’s own identity. Identity is a personal internal space, built on the basis of empathy, autonomy, distance, assertiveness, activity, and tolerance. Identity is different dimensions of individuality, uniqueness and separate- ness, compatibility of thoughts-feelings-actions, self-esteem and intentionality important for inter- personal and social conflicts. It serves to build and consolidate an image of oneself and knowledge about oneself. Identity allows a person to self-reflect, receive insight, evaluate, make changes, and strengthens the image of his/her person, offering a sense of separateness and being yourself.